ASAS PEMBALIKAN BEBAN PEMBUKTIAN TERHADAP TINDAK PIDANA KORUPSI DALAM SISTEM HUKUM PIDANA INDONESIA DIHUBUNGKAN DENGAN KONVENSI PERSERIKATAN BANGSA-BANGSA ANTI KORUPSI 2003 - Lilik Mulyadi (Jurnal Hukum dan Peradilan, 2015)
This article describes some problems of the result of research regarding the shifting of burden of proof upon corruption offences in the Indonesian system of criminal law with regards UN Convention Against Corruption (UNCAC) 2003. There are two basic questions which become the research objections, firstly: to what extent the shifting of burden of proof has been implemented in the criminal court regarding corruption cases, and secondly, to what extent does the legislation policy apply for the shifting of burden of proof in relation with UNCAC 2003. The article uses normative research which regulation, conceptual, case and comparative approach. Such research emphasizes interpretation and legal construction to obtain some legal norms, conception, regulation list and its implementation in concreto cases. Regulation and conceptual approach to used how to know, existention, consistency and harmonization regarding the shifting of burden of proof upon corruption offences in legislation body. The cases approach uses comparative law regarding the reversal burden of proof upon corruption offencer between Indonesia and the other countries. This research shows that the shifting of burden of proof has never yet applied for in the corruption cases Indonesia. Those experiences is not similar with the experiences of against corruption Hong Kong and India, wihich implement the reversal burden of proof by using some approach socalled balanced probability of principles in the relation to the property or asset of defendant comes from. The Indonesian corruption regulation policy, especialy article 12B, 37, 37A, 38B apparently it’s not cleaq and disharmony to norm of sudden charge of fortune the shifting of burden of proof formulation in connection with United Nations Convention Against Corruption 2003(KAK 2003). So, necessary (needs) of modification sudden charge of fortune shifting of burden of proof formulation which preventive, represive and restorative characteristic.  Keywords: Shifting the Burden of Proof, Corruption Offences, Criminal Justice System